PELATIHAN PENCATATAN TRANSAKSI BISNIS PERUSAHAAN JASA BAGI SISWA BINAAN RUMAH BELAJAR MAHKOTA KASIH INSANI - Henny Henny; Clarrisa Ervina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Covid-19 Pandemic period made students have to study online, so that students' absorption of the knowledge provided by the school was less comprehensive, and made the students of the Mahkota Kasih Insani Learning House need extra education related to the subjects they studied at school, one of which was accounting lessons. Accounting for these students is the subject that makes students the most bored of studying. Therefore, partners need strategies on how to study accounting that is attractive to students. Based on this background, the Mahkota Kasih Insani Learning House collaborates with external parties, namely Universitas Tarumanagara to provide community service in the field of accounting. The purpose of this community service activity is training in recording service company business transactions for students assisted by the Mahkota Kasih Insani Learning House. The method used in this activity is an offline training method. The implementation of community service activities was carried out on Saturday, October 9, 2021 by implementing strict health protocols, because these activities were carried out offline so that students easily understood the material provided by the community service implementing team. The conclusion of the implementation of this activity is the need for a strategy on how to learn accounting that attracts students in recording business transactions of service companies which is one of the topics in the accounting field. Based on the results of the evaluation, the assisted students said that the implementation of this activity could take place every semester with a different topic and in accordance with the material they learned at school online.